2011
DOI: 10.1038/aja.2010.158
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone positively regulates steroidogenesis via extracellular signal-regulated kinase in rat Leydig cells

Abstract: Gonadotropin-releasing hormone (GnRH) is secreted from neurons within the hypothalamus and is necessary for reproductive function in all vertebrates. GnRH is also found in organs outside of the brain and plays an important role in Leydig cell steroidogenesis in the testis. However, the signalling pathways mediating this function remain largely unknown. In this study, we investigated whether components of the mitogen-activated protein kinase (MAPK) pathways are involved in GnRH agonist (GnRHa)-induced testis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“… 29 Our previous study demonstrated that the synthesis of annexin A5 is stimulated by GnRH and hCG, and GnRH positively regulates steroidogenesis by activating ERK in rat Leydig cells. 18 30 ERK1/2 but not JNKs or p38-MAPKs was activated by GnRH in our previous study, 30 and ERK1/2 is also activated by annexin A5 in the current study. Interestingly, JNKs or p38-MAPKs were not activated by annexin A5 in our study.…”
Section: Discussionsupporting
confidence: 62%
“… 29 Our previous study demonstrated that the synthesis of annexin A5 is stimulated by GnRH and hCG, and GnRH positively regulates steroidogenesis by activating ERK in rat Leydig cells. 18 30 ERK1/2 but not JNKs or p38-MAPKs was activated by GnRH in our previous study, 30 and ERK1/2 is also activated by annexin A5 in the current study. Interestingly, JNKs or p38-MAPKs were not activated by annexin A5 in our study.…”
Section: Discussionsupporting
confidence: 62%
“…Testicular GnRH receptors have been reported in several species, including humans (87,88). In rats, GnRH affects Ca 2+ mobilisation (89) as well as steroidogenesis in Leydig cells (90). This reported direct effect of GnRH on steroidogenesis is especially noteworthy for the present study because, although testosterone implants returned testosterone concentrations to the normal range in castrated rats, the elevation in testosterone was lower in deslorelin‐treated intact rats.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin V and 3-β-hydroxysteroid dehydrogenase (HSD) were also shown to colocalize in the Leydig cells16. Our previous studies showed that GnRH agonist increased the mRNA and protein levels of annexin V in primary rat Leydig cells in vitro 17, as well as the secretion of testosterone18, annexin V could increase testosterone production and promote cell proliferation of Leydig cells. During the puberty, the proliferation of Leydig cell precursors is required to increase the number of Leydig cells.…”
mentioning
confidence: 96%